Investigation of microRNA expression in thyroid carcinoma among South Africa patients - Mokhesi, Neo (Division of Anatomical Pathology, 2018)
Objective: Thyroid cancer affects approximately 298 million people worldwide and the major challenge is reliably distinguishing patients who present with poor prognosis from those who do not. There are genetic markers that have been shown to be associated with poor clinical outcome in thyroid cancer, which include mutations in the BRAF and RAS genes. In addition to genetic variation, recent studies have reported on the effects of micro-ribonucleic acids' (miRNAs) differential expression observed in tumour and normal tissue as another possible marker of thyroid cancer prognosis. Therefore, miRNA expression signatures in thyroid cancer could be used as biomarkers for prognosis and diagnosis. This study compared the expression of miRNAs in papillary thyroid cancer and follicular thyroid cancer. Methods: As part of a preliminary study, 66 differentiated thyroid cancer samples were obtained from patients attending Groote Schuur Hospital and used in the study. MiRNA miScript polymerase chain reaction (PCR) Array (Qiagen) was used to determine the differential miRNA expression profiles between follicular thyroid carcinoma (FTC) and papillary thyroid carcinoma (PTC). Real time PCR was employed to confirm the expression levels of miRNA- 21 and miRNA-122. Results: 17 miRNAs were upregulated in PTC and 14 in FTC. There were significant differences in the miRNA expression between FTC and PTC. For example, miRNA-21 was the most upregulated miRNA in PTC and miRNA-122 in FTC. We found no correlation of the expression of these miRNAs to clinicopathological features. We observed an association of BRAF mutation positivity to advanced tumour stage and advanced age of presentation however, no correlation was seen to miRNA-21 or miRNA-122 expression. Conclusion: Although we did not observe correlations between miRNAs and any of the clinicopathological features, microRNA expression profile signatures were able to differentiate between PTC and FTC and could potentially be further validated as diagnostic markers.